PERANAN KEPEMIMPINAN MELAYANI DALAM UPAYA MENINGKATKAN KINERJA GURU - Hendrayadi Hendrayadi; Yunus Yunus (STKIP Pesisir Selatan, 2026)
Lack of competence will have an impact on the quality of education. In addition to teacher competence or performance, principal leadership also affects quality, so principals must be innovative in finding strategies to improve teacher performance. This study aims to determine the technique of improving teacher performance by the Principal at SMP Negeri 4 Malangke City. This research is a qualitative research that uses a phenomenological approach. Sources of data, namely primary data sourced from school principals, deputy principals, teachers. Meanwhile, secondary data were taken from documents related to the research. The instrument used in collecting data is the researcher himself who functions to determine and select informants as data sources, analyze data, interpret data, and the instruments in collecting data are observation, interviews, and documentation. The results of the study indicate that service leadership is; Listening, Empathy, Conceptualization have been implemented in SMP Negeri 4 Malangke City. Principals in an effort to improve teacher performance, (1) conduct teacher development; (2) support teachers to take part in seminars, training, research activities; (3) implementing a system of rewards and appreciation for the achievements of teachers; (4) improvement of teacher welfare for honorary teachers.